'Paramedic decision-making in out of hospital cardiac arrest. A descriptive phenomenological study' - Karl Charlton; Mark Bevan (Elsevier, 2024)
During out of hospital cardiac arrest paramedics make decisions to commence, continue or terminate resuscitation. There is variability in when resuscitation is provided, and evidence suggests these decisions are complex and influenced by factors other than patient clinical characteristics. Through first-hand accounts of paramedics who bear witness to, and make, life and death decisions during out of hospital cardiac arrest, this study aimed to describe how paramedics decide to provide resuscitation.This descriptive phenomenological study involved eight participants and was conducted between April-September 2021 in North East Ambulance Service NHS Foundation Trust.Paramedic stories and reflections on their encounters with out of hospital cardiac arrest speak of how the role of paramedic is bound to Selfhood and public identity, uncertainty about when death has occurred versus a sudden reversible event, the ethics and morality of an obligation to Others and the plurality of lifeworld.Resuscitation has significant ritualistic value, is often delivered in light of expectation and serves important social functions in the process of death recognition, Selfcare and care for Others. Further research is needed to understand the impact variability in decision-making has on patient outcomes and how this relates to patient and public expectations.